2019
DOI: 10.1080/14712598.2019.1645114
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety, efficacy, and immunogenicity of adalimumab biosimilar BI 695501 and adalimumab reference product in patients with moderately-to-severely active rheumatoid arthritis: results from a phase 3b extension study (VOLTAIRE-RAext)

Abstract: Objective: To evaluate long-term safety, efficacy, and immunogenicity of BI 695501 in patients with moderately-to-severely active rheumatoid arthritis (RA) who have completed VOLTAIRE-RA. Methods: Eligible patients for this phase 3b open-label extension study (VOLTAIRE-RAext), who had completed 48 weeks' treatment with BI 695501 (Group A), 24 weeks each of adalimumab RP then BI 695501 (Group B), or 48 weeks of adalimumab RP (Group C) in VOLTAIRE-RA, were enrolled. Results: Altogether, 430 patients received BI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 20 publications
2
36
0
1
Order By: Relevance
“…BI 695501 was approved by the EMA and FDA in 2017. Previous research has confirmed its similarity in structure, function, and PK to ADL (15,16).…”
Section: Bi 695501 (Cyltezo)mentioning
confidence: 72%
“…BI 695501 was approved by the EMA and FDA in 2017. Previous research has confirmed its similarity in structure, function, and PK to ADL (15,16).…”
Section: Bi 695501 (Cyltezo)mentioning
confidence: 72%
“…The treatment efficacy established in the main trial was maintained throughout the OLE, and no new safety signals were identified. No differences in efficacy, safety, or immunogenicity were seen among the treatment groups [20].…”
Section: Bi 695501mentioning
confidence: 89%
“…In a long-term OLE, patients who previously received BI 695501 for 48 weeks were assigned to a group (n = 225), patients who previously received adalimumab RP for 24 weeks and were switched to BI 695501 were assigned to another group (n = 102), and patients who previously received adalimumab RP for 48 weeks were assigned to a third group (n = 103). All patients received BI 695501 40 mg/0.8 ml solution every 2 weeks for up to 48 weeks (treatment duration 98 weeks) [20]. The treatment efficacy established in the main trial was maintained throughout the OLE, and no new safety signals were identified.…”
Section: Bi 695501mentioning
confidence: 99%
“…To date, the FDA has not considered any biosimilar as interchangeable. 45 Although several phase III RCTs or open label extension studies on switching from reference adalimumab to the respective biosimilars or multiple switching between groups showed comparable safety, efficacy and immunogenicity, 15,20,21,26 evidence on the nonmedical switching from reference adalimumab to the respective biosimilars in the real-world setting is limited and is mostly based on a few small-scale observational studies with a limited number of subjects, thus seemingly insufficient to recommend this switching procedure. Safety data from real-world practice are available only for SB5.…”
Section: Interchangeability With Reference Adalimumabmentioning
confidence: 99%